HUBUNGAN INTENSITAS CAHAYA DAN KELEMBABAN RUANGAN DENGAN KELELAHAN KERJA PADA KARYAWAN DI UNIVERSITAS PENDIDIKAN MANDALIKA TAHUN 2021 - Ayu, Baiq Fathin; Solo, Yulita (Aspiration of Health Journal, 2023)
Work fatigue is a condition where a person gets physical weaknesses or is no longer able to do his job. Work fatigue can occur because of an unsupported environment. The purpose of this study was to know the relationship between light intensity and room humidity toward work fatigue on employees at Mandalika University of Education in 2021.Design of the study was analytic observational by using cross sectional approach. The number of samples was 62 samples. Analysis of data used is univariate analysis, bivariate using Chi Square test. Based on the analysis in this study between light intensity variable and work fatigue on employees got a p value=0.061 can be interpreted that there was not any relationship between the both variables, whereas between room humidity variable and work fatigue on employees got a p value=0.282 meant that there was not any relationship between the both variables. The conclusion of the study was there was not any relationship between light intensity and room humidity toward work fatigue on employees at Mandalika University of Education in 2021.It is suggested to the Rector of UNDIKMA is to add lighting sources and humidity to make the room temperature ideal with the aim of improving employee performance at UNDIKMA.